Blowing sikus beyond Titicaca: sikuri groups as islands of the trans-Andean cultural archipelago in Buenos Aires, Santiago, and Bogotá (Revista de Crítica Literaria Latinoamericana, 2014)
In this article I suggest studying the exponential rising of sikuri ensembles in Buenos Aires, Santiago and Bogota as an integral part of a counter-hegemonic social movement. Particularly, I propose that the sonorities, discourses, and practices with which the sikuris intervene and appropriate those spaces, further complicate their urban experiences and transform these cities into "islands" of an extensive cultural archipelago whose dimensions transcend the national and geographic boundaries that are often imagined as an attribute of "lo andino." In this sense, the multi-directional flow of people, music, and ideas contribute to the consolidation of a transnational community that, being as heterogeneous as it may be conceived, imagines itself united by a set of sounds, symbols, discourses, and practices that form part of the organic development of a larger Utopian project: a new Pachacuti.
Keywords: sikuris; ethnogenesis; transculturation; transandean cultural archipelagoes; Juan Zevallos; proactive nostalgia; Pachacuti